Extremely low frequency ion cyclotron resonances on the surface boundaries of coherent water domains. Issue 1 (September 2021) - Widom, A; Swain, J; Valenci, V I
Abstract: Pure Water under standard pressure, temperature and dilute solution conditions contain coherent Preparata-Del Giudice domains approximately a tenth of a micron in size. Ions of charge q = Z e can be confined to the surface boundaries of coherent water domains. Solving for the motion of ionic charges confined to surfaces in a uniform magnetic field B = curlA it is shown that there exist resonances scaled by the ionic cyclotron frequency ω c = (qB/Mc) . The surface classical ionic motions described by the vector potential lagrangian L = (M/2)v μ Vμ + (q/c)v μ Aμ are integrable for a spherically symmetric surface. The resulting extremely low frequency (ELF) resonant modes are only weakly damped by fluid viscosity due to the small length scales of the confining surface and these modes are of importance in biophysical processes.